Perjamuan Kudus dan Idul Adha Sebagai Dasar Teologi bagi Rekonsiliasi Hubungan Kristen dan Islam di Indonesia - Siregar, Christian (Bina Nusantara University, 2014)
This paper is intended as an alternative to solving the problem of conflict that often occurs between the two religious missions in Indonesia, Islam and Christianity. The solution offered is to reflect on and interpret the meaning of two great celebrations in the tradition of Islam and Christianity, Eid ul-Adha and the Lord's Supper, which is shared with others. A theological review is required to complete a philosophy of our country, Pancasila, so that the reconciliation which is basicly desired by all religions in Indonesia can be realized with sustainably. Religious-Islam and Christian-side by side can build a more prosperity dan peaceful life. Discussion in this paper is based on a review of selected literature which is relevant to the topic and up to date. From the results of the study it can be concluded that forgiveness is a courage act that needed, which can bring about reconciliation among Christians-Islam by re-purposing the celebration of Holy Communion and Eid al-Adha.